Production of monoclonal antibody specific for human hemoglobin - (:unkn) unknown (My University, 2001)
Hemoglobin is not normally present in sputum, urine or feces except in minute amounts. Demonstration of the presence of hemoglobin in these materials is an important diagnostic clue that usually implies bleeding within the respiratory, urinary or gastroentestinal tract, respectively. In this work, a hybridoma line secreting monoclonal antibody (Mab) highly specific for human hemoglobin A (hHbA)was generated by fusion of immunized BALB/c mouse splenic lymphocytes with non-secreting mouse myeloma cells followed by selection in hypoxanthine-aminopterin-thymidine (HAT) medium and the screening of culture fluids for hHb A affinity in ELISA. The Mab produced by MAM 2/3B6 is highly specific to hHbA and did not react with heterologous hemoglobin species. The sensitivity of the immune test systems based on the produced Mab was found to be 0.1 μg/of hHb per ml.
Keywords: ELISA; Human hemoglobin; Immunodiagnosis; Monoclonal antibody